IMPLEMENTASI MEDIA PEMBELAJARAN BERBASIS CANVA CODE 2.0 UNTUK MENINGKATKAN HASIL BELAJAR SISWA SMK - Inarotul Caturmufidarini; Erika Fataa Cahyaningrum; Enistia; Jarot Tri Bowo Santoso; Kardiyem (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effect of using Canva Code 2.0-based learning media on the learning outcomes of 11th grade students majoring in Office Management and Business Services at a private vocational school in Semarang. The method used is a quantitative pre-experimental approach with a one-group pretest and posttest design. The experimental population consisted of 36 students. However, due to field conditions, the pretest and posttest were administered to 33 students. The experimental research procedure included the administration of a pretest, the provision of treatment in the form of Canva Code 2.0 learning media, followed by a posttest. The data obtained will be analyzed using normality tests, paired sample t-tests, and N-Gain tests. The results showed that the Canva Code 2.0 learning media was quite effective in improving students' understanding of the material and motivation to learn, as well as being able to help achieve learning objectives in an interactive and fun way. In conclusion, Canva Code 2.0 learning media can be used as an innovative alternative in digital learning in the modern era. Further research is recommended to explore the long-term impact of using Canva Code 2.0 on learning motivation, learning outcome sustainability, and media application. Keywords: Learning Media, Canva Code 2.0, Learning Outcomes